EXPLORATORY ANALYSIS OF ATMOSPHERIC MODELLING USE OVER PANTANAL WILDFIRES - Couto, Flavio Tiago; Santos, Filippe Lemos Maia; Campos, Cátia; Purificação, Carolina; Andrade, Nuno; Lopez-Vega, Juan Manuel; Lacroix, Matthieu (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
The study discusses in an exploratory way the atmospheric conditions leading to several fires in the Pantanal on November 12, 2023. These episodes were marked by two periods of maximum fire expansion, first in the early afternoon and another in the evening. The study is based on a set of observations from satellites and weather stations, which helped to identify these fires and some meteorological conditions at the surface. In addition, the Fire Weather Index (FWI) in the Pantanal was analyzed for a 44-year period. However, this dataset was not enough to completely explain the fire behavior on that day. In this context, atmospheric modeling was applied to find the possible causes of fire behavior in these two periods. The Meso-NH model was run with two nested domains of horizontal resolutions of 2500 m and 500 m. The results showed a positive trend of FWI in the last decades and a clear seasonality for the maximum values in 2023. Also, the simulation indicated favorable weather conditions for fire ignition, given the high temperatures and low relative humidity. However, the wind gust field showed moderate gusty winds in both periods but caused by different forces. In the early afternoon, the larger scale circulation favored fire propagation, whereas in the evening fire spread by a gust front. Furthermore, the findings highlight the role of weather conditions on a sub-daily scale, with sudden changes in surface winds throughout the day, which is strongly recommended to be considered when examining fire danger and firefighting action plans in the region.